1993
DOI: 10.1063/1.354768
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of copper indium diselenide by selenization of copper indium oxide

Abstract: A process is reported for preparation of thin films of copper indium diselenide (CIS). This process involves two steps: (a) formation of Cu2In2O5 by spray pyrolysis and (b) reaction of Cu2In2O5 with selenium vapor to form CIS. The purity of the CIS prepared by this method can approach that of the material prepared by vacuum deposition methods because highly purified water and nitrate salts can be used in the spray pyrolysis step, and the purity of the selenium used in the second step can be identical to that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Except for sample E (not shown), in which the sulfurization process was applied after each coating cycle, no delamination upon fracturing can be detected by SEM. This, considering also the surface free of cracks and pinholes, is an indication of sufficient adherence to the substrate 4 Micrographs of the cross-sections of samples A3 (a) and D (b) and morphology of film B1 (c) and B2 (d) surfaces. …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Except for sample E (not shown), in which the sulfurization process was applied after each coating cycle, no delamination upon fracturing can be detected by SEM. This, considering also the surface free of cracks and pinholes, is an indication of sufficient adherence to the substrate 4 Micrographs of the cross-sections of samples A3 (a) and D (b) and morphology of film B1 (c) and B2 (d) surfaces. …”
Section: Resultsmentioning
confidence: 95%
“…The color change to transparent with a very slight brownish hue suggests that the Cu(0) is oxidized to Cu(I) . Hence it can be concluded that prior to sulfurization the films are composed mainly of Cu(I) and In(III) amorphous oxides, although the presence of a small amount of Cu(II) cannot be excluded …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[68,69] Power conversion efficiencies of up to 5 % have been reported using this approach. [70] The main impediment to higher efficiency in devices prepared using these approaches appears to be achieving adequate phase and compositional purity (e.g., inclusion of impurities from the solvent, precursor or atmosphere).…”
Section: Non-vacuum Deposition Methodsmentioning
confidence: 99%